Application of a natural-light stereoscopic 3D display for interactive digital teaching - Tian, Peng. (2009)
Nowadays, 3D technology has been being widely used for multi-group presentations as well as individual entertainment, including theatre shows and home video display. Therefore, there are great opportunities in the markets to grow. Moreover, Singapore Government is currently boosting the scientific teaching at its primary and secondary schools. Therefore, the project was proposed and developed to cooperate with the interactive digital teaching at these schools. In order to complete a functional and thorough 3D display system with a low cost, it requires hardware, software applications and animation production to work together with the LCD technology.